In vitro apoptosis induction and inhibition of NF-kB signaling pathway by biseugenol B in PC3 human prostatic cancer cells / Maryam Abbaspour Babaei - Maryam, Abbaspour Babaei (2018)
Prostate cancer is considered as the second most common cancer across the world in men. Apoptosis induction in prostate cancer cells (PC3) revealed an efficient therapeutic strategy for cancer therapy. The conventional cancer treatment approach including chemotherapy and radiotherapy cause severe adverse effects and treatment failure. Given the drawbacks of modern cancer medicines, the search for new synthetic agents from medicinal plants and natural compounds is emerging. Recent phytochemical investigation and clinical studies have shown the potential anti-cancer value of natural compounds. Recent studies have shown selective cytotoxicity of biseugenol B in PC3 cells compared to other cancer cell lines. Therefore, there is a need to evaluate if this natural compound possesses potential anticancer activity. The aim of the study is to evaluate the apoptosisinduction effect of 2, 2’-oxybis (4-allyl-1-methoxybenzene), biseugenol B, a natural compound from Litsea costalis, on human prostate cancer cell line (PC3) via activation of extrinsic, intrinsic and inhibition of NF-κB signaling pathways using an in vitro model. The potential therapeutic activity of biseugenol B, isolated from Litsea costalis to inhibit human prostate cancer cells PC3 through apoptosis was evaluated in vitro. In this study, the cell death mechanism of biseugenol B was investigated. MTT assay was used to evaluate biseugenol B-induced cell viability. The apoptosis effect of biseugenol B in PC3 cells were confirmed by using double-staining propidium and acridine orange and AV-FITC staining. Cell cycle arrest was examined using flow cytometry whilst protein and the expression level of mRNA Bcl-2, Bax, and HSP70 were assessed using Western blotting and RT-PCR. Cell permeability, nuclear condensation, release of cytochrome c and mitochondrial membrane potential (MMP) were observed in PC3 cells treated with biseugenol B using high content screening (HCS). The level of caspase-3/7, -8 and -9 were examined and the activity of NF-κB was evaluated using HCS assay. iv Biseugenol B showed a significant cytotoxicity (IC50 < 5 µg/mL) towards human prostate cancer cells (PC3) when compared to normal human prostate cells (RWPE-1). Propidium and acridine orange double-staining and AV-FITC staining results showed a significant apoptosis induction effect of biseugenol B in PC3 cells. Early apoptosis cells significantly increased in PC3 cells with exposure to different dose of biseugenol B (P < 0.001). The results indicated that a number of the cells in sub-G0 phase were significantly increased after exposure to different dose of biseugenol B (P < 0.001). The results demonstrate that biseugenol B significantly increased the cell arrest of PC3 in G0/G1 phase after exposure with different dose of biseugenol B. A significant up-regulation of Bax and down-regulation of Bcl-2 and Hsp70 were observed (P < 0.001). Meanwhile caspases-3/7, caspase-8 and caspase-9 levels were noted to be significantly increased (all P-values < 0.001). The translocation of NF-κB from the cytosol to the nucleus was significantly inhibited (P < 0.01) by biseugenol B. Our findings suggest that biseugenol B could potentially induce apoptosis in prostate cancer cells and thus serve as a promising compound in the prostate cancer treatment.